Drag reducer for oil and gas gathering and transportation and application thereof
By combining the combination of two specific polymer molecules, the oil and gas collection and transportation drag reducing agents are solved, and the existing drag reducing agents are prone to fracture in high shear areas, significantly improving their shear resistance and drag reduction rate, extending the duration of the drag reduction effect, and reducing transportation costs.
Patent Information
- Application Number
- CN202411757613.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing drag reducing agents in the elbows, valves and other parts in the pipeline are broken due to the shearing effect of the polymer molecular chain, resulting in a reduction in the drag reducing effect, which requires frequent replenishment, resulting in a large consumption.
The oil and gas collection and transportation drag reducing agent is prepared by combining the combination of two specific polymer molecules. Hexadecimal methacrylate, ethylene glycol mono-9-octadecene-1-ether, allyl triethylammonium chloride and other raw materials are used to form high molecular weight nanocomposite polymers, enhancing its shear resistance and drag reduction rate.
The shear resistance of the drag reducer in the high shear area is significantly improved, reducing the fracture of covalent bonds, extending the duration of the drag reduce effect, reducing transportation costs, and improving oil transport stability and pipeline conveying capacity.
Smart Images

Figure BDA0005166736870000201
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of oil and gas field exploitation, and in particular to a drag reducing agent for oil and gas gathering and transportation and its application. Background Art
[0002] In recent years, my country's oil pipeline construction has achieved rapid development, and a pipeline transportation network has gradually been formed. Since the oil pipeline is long, any consumption during the transportation process will cause a large amount of energy consumption through accumulation. Therefore, it is very important to ensure the safe and efficient operation of the oil pipeline.
[0003] In order to maximize the transportation volume of crude oil and various refined oil products during long-distance transportation, reduce transportation time and transportation costs, the oil industry uses drag reduction technology to reduce the energy consumption of oil pipeline transportation. Drag reducer is a lubricant that can reduce pipeline resistance and friction resistance. Its main function is to improve the fluidity of oil products, reduce pressure loss, reduce energy consumption, and improve oil transportation efficiency. Due to the small amount of drag reducer, significant effect, and little effect on the properties of oil products, it has been rapidly applied on a large scale. Adding drag reducer can effectively reduce the friction resistance of the transportation pipeline, quickly and economically improve the pipeline transportation capacity, and increase the pipeline transportation volume. Therefore, it is of great significance to accelerate the development and utilization of petroleum products.
[0004] However, the drag reducing effect of existing drag reducers is only effective for straight pipes. For elbows, valves, booster pumps and other parts in the pipeline, the polymer molecular chains are easily sheared and broken and degraded when passing through, thereby reducing the drag reducing effect. In order to ensure the stability of oil transportation in the oil pipeline and reduce transportation costs, drag reducers need to be continuously replenished during long-distance pipeline transportation, resulting in a large consumption of drag reducers. Summary of the invention
[0005] The present application aims to overcome at least one of the defects of the prior art and provide a drag reducer for oil and gas gathering and transportation and its application. The drag reducer for oil and gas gathering and transportation prepared by the association of two specific polymer molecules has strong shear resistance and high drag reduction rate.
[0006] In the first aspect, the embodiment of the present application provides a drag reducing agent for oil and gas gathering and transportation, which is achieved by the following technical solutions:
[0007] A drag reducing agent for oil and gas gathering and transportation, comprising a first polymer molecule and a second polymer molecule, wherein the first polymer molecule and the second polymer molecule are combined by intermolecular association;
[0008] The first polymer molecule comprises the following raw materials in parts by weight: 25-30 parts of hexadecyl methacrylate, 12-18 parts of ethylene glycol mono-9-octadecene-1-ether, 6-10 parts of allyl triethylammonium chloride, 0.1-0.3 parts of azobisisoheptonitrile, 0.5-1 parts of polyethylene glycol monooctylphenyl ether, 1-2 parts of hydroxyethyl cellulose, 2-3 parts of modified nano-alumina, and 10-12 parts of an interfacial compatibilizer;
[0009] The second polymer molecule comprises the following raw materials in parts by weight: 25-30 parts of hexadecyl methacrylate, 12-18 parts of p-propanesulfonic acid styrene, 5-8 parts of 3,7-dimethyl-6-octenoic acid, 0.1-0.3 parts of azobisisoheptonitrile, 0.5-1 parts of polyethylene glycol monooctylphenyl ether, 1-2 parts of hydroxyethyl cellulose, 2-3 parts of organically modified nano-diatomaceous earth, and 10-12 parts of an interfacial compatibilizer.
[0010] A drag reducing agent for oil and gas gathering and transportation according to an embodiment of the present application has at least the following beneficial effects:
[0011] The drag reducer of the present application includes a first polymer molecule and a second polymer molecule, which are bonded by intermolecular association, including not only hydrogen bonding between hydroxyl groups and carboxyl groups and sulfonic acid groups, but also ionic bonding and electrostatic adsorption bonding between quaternary ammonium salts and carboxyl groups and sulfonic acid groups. The association bonding increases the size of the molecular cluster. When passing through a high shear region, the shear force borne is shared compared with a chain of polymer molecules. Since hydrogen bonds and ionic bonds break before covalent bonds, the number of covalent bond breaks is reduced. When passing through a low shear region, hydrogen bonds and ionic bonds will automatically associate and reduce, thereby achieving the purpose of anti-shear.
[0012] The side chains of the drag reducer molecules of the present application contain longer side chains and benzene rings. Longer side chains increase their flexibility and enable them to fully stretch in the pipeline, thereby enhancing their shear resistance and drag reduction performance. The benzene ring is a rigid monomer with very strong shear resistance. The combination of long side chains and benzene rings can significantly improve the drag reduction effect while increasing the molecular weight. In addition to long side chains and benzene rings, the introduction of quaternary ammonium salts, hydroxyl groups, ether bonds, carboxyl groups, sulfonic acid groups and other groups can also facilitate the adjustment of the solubility of the drag reducer molecules. The polymer drag reducer can only show a good drag reduction effect if it is uniformly dissolved in the fluid. If the solubility is too strong, the drag reduction effect will be obvious in the initial stage of addition, but the drag reduction effect will not be sustained after a period of degradation. If the solubility is poor, polymer crystallization will occur, affecting the opening of the molecular chain and the drag reduction effect.
[0013] The polyethylene glycol monooctylphenyl ether in the present application is a nonionic emulsifier, and hydroxyethyl cellulose is an emulsifying dispersant. The addition of the two can improve the polymerization quality of the product, increase the molecular weight and uniformity, thereby increasing the viscosity of the product, and at the same time can further enhance the drag reduction effect.
[0014] The present application introduces inorganic nanoparticle-modified nano-alumina and organically modified nano-diatomaceous earth into the drag reducer to form a nano-composite polymer. These nanoparticles can increase the rigidity and strength of the polymer, thereby further improving the shear resistance of the drag reducer.
[0015] According to some embodiments of the present application, the weight ratio of the first polymer molecules to the second polymer molecules is (1.1-1.2):1.
[0016] According to some embodiments of the present application, the preparation of the first polymer molecule comprises the following steps:
[0017] A1. According to parts by weight, hexadecyl methacrylate, ethylene glycol mono-9-octadecene-1-ether, allyl triethylammonium chloride, polyethylene glycol monooctylphenyl ether, and hydroxyethyl cellulose were mixed and added to toluene, stirred at a speed of 300-500r / min, nitrogen protective gas was introduced, azobisisoheptanenitrile was added at a temperature of 70-90°C, the reaction was stopped after 10-12h of heating, and an appropriate amount of anhydrous ethanol was added after cooling. After precipitation and separation, it was washed with anhydrous ethanol several times, and dried to constant weight under vacuum conditions at 60°C to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride;
[0018] A2. Add the interfacial compatibilizer to the n-heptane solution of the polymer hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride according to parts by weight, then add the modified nano-alumina, mix well, and react with low-speed stirring at 60-80°C for 1-2h to obtain the first polymer molecule.
[0019] According to some embodiments of the present application, the preparation of the second polymer molecule comprises the following steps:
[0020] B1. Hexadecyl methacrylate, p-propanesulfonic acid styrene, 3,7-dimethyl-6-octenoic acid, polyethylene glycol monooctylphenyl ether, and hydroxyethyl cellulose were mixed and added to toluene in parts by weight, stirred continuously at a speed of 300-500 r / min, nitrogen protective gas was introduced, azobisisoheptanenitrile was added at a temperature of 70-90°C, the reaction was stopped after 10-12h of heating, and an appropriate amount of anhydrous ethanol was added after cooling, and the mixture was precipitated and separated and then washed with anhydrous ethanol several times, and dried to constant weight under vacuum conditions at 60°C to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid;
[0021] B2. Add the interfacial compatibilizer to the n-heptane solution of the polymer hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid according to weight parts, then add the organically modified nano-diatomaceous earth, mix well, and react with low-speed stirring at 60-80° C. for 1-2 hours to obtain the second polymer molecule.
[0022] According to some embodiments of the present application, the preparation of the modified nano-alumina comprises the following steps:
[0023] S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water (8-9):1 by mass ratio, and adding glycidyloxypropyl trimethoxysilane coupling agent under stirring, raising the temperature to 70-80°C, constant temperature magnetic stirring for 5-8h, centrifuging, washing, and drying to obtain organosilicon-modified nano-alumina;
[0024] S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0025] S3. Add the graphene pretreated in step S2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano-alumina prepared in step S1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano-alumina.
[0026] Modified nano-alumina is used as a filler in nano-composite polymers. Nanomaterials can enhance the mechanical properties of polymers due to their large specific surface area and high adsorption performance; alumina can effectively improve rigidity, antioxidant and corrosion resistance; silicone can increase the dispersion of nano-alumina in monomers, improve the rigidity and corrosion resistance of nano-composite polymers; after graphene is acidified, its surface will be oxidized into carboxyl groups, which will combine with silicone-modified nano-alumina, reducing the problem of graphene agglomeration. The layered structure of graphene allows for more complete mixing between filler and resin, thereby improving the shear strength of nano-composite polymers.
[0027] Furthermore, the weight ratio of the nano-alumina, the anhydrous ethanol and the glycidyloxypropyltrimethoxysilane coupling agent is 1:(8-10):(0.1-0.2).
[0028] Furthermore, the average particle size of the nano-alumina is 50-200nm.
[0029] According to some embodiments of the present application, the preparation of the organically modified nano-diatomite includes the following steps: dissolving the nano-diatomite in deionized water, adding a Na2CO3 solution dropwise while stirring until the pH value stabilizes at 10, and simultaneously adding propylene glycol alginate and letting it stand to obtain a stable suspension, heating to 120-150°C, adding hexadecyltrimethylammonium bromide solution and isopropanol, reacting for 5-8h to obtain a modified diatomite suspension slurry, centrifuging to obtain a diatomite precipitate, washing away excess Br ions with an ethanol solution, using AgNO3 to check that no yellow precipitate is produced, drying and grinding to obtain the organically modified nano-diatomite.
[0030] Furthermore, the weight ratio of the nano-diatomaceous earth, the hexadecyltrimethylammonium bromide solution and the isopropanol is 1:(1-2):(0.5-0.8).
[0031] Furthermore, the amount of propylene glycol alginate is 1% of the weight of the nano-diatomaceous earth.
[0032] Furthermore, the mass percentage concentration of the Na2CO3 solution is 20-30%.
[0033] Furthermore, the stirring speed is 2000-3000r / min.
[0034] According to some embodiments of the present application, the preparation of the interfacial compatibilizer includes the following steps: taking poly-α-olefin, adding anhydrous ethanol to completely disperse it, using an ultrasonic cell crusher to ultrasonically crush it for 5-10 minutes, adding maleic anhydride dried for 6-12 hours, and continuing ultrasonication for 10-30 minutes to obtain poly-α-olefin grafted with acid anhydride as an interfacial compatibilizer.
[0035] Furthermore, the weight ratio of the poly-α-olefin to the maleic anhydride is 100:(2-4).
[0036] In a second aspect, the embodiments of the present application provide the application of the above-mentioned drag reducer for oil and gas gathering and transportation in oil product gathering and transportation.
[0037] The drag reducer of the present application is used in oil gathering and transportation, and can effectively reduce the friction resistance of the transportation pipeline, quickly and economically improve the pipeline transportation capacity, and increase the pipeline transportation volume. Since the drag reducer is not easily broken by shearing, it can better ensure the oil transportation stability of the oil pipeline and reduce transportation costs.
[0038] According to some embodiments of the present application, the specific application method is as follows: the first polymer molecule and the second polymer molecule are mixed according to a weight ratio, and a certain amount of oil is added to dissolve, and the amount of the oil can dissolve the drag reducer, and then the drag reducer oil solution is injected into the oil gathering pipeline;
[0039] The amount of the drag reducer added to the oil gathering and transportation pipeline is 10-1000ppm.
[0040] Furthermore, the oil product includes crude oil, gasoline, kerosene or diesel. DETAILED DESCRIPTION
[0041] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.
[0042] Example 1
[0043] Preparation of drag reducing agent for oil and gas gathering and transportation:
[0044] (1) Preparation of the first polymer molecule: 28 parts of hexadecyl methacrylate, 15 parts of ethylene glycol mono-9-octadecene-1-ether, 8 parts of allyl triethylammonium chloride, 0.8 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried under vacuum conditions at 60° C. to constant weight to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride; 11 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride, and 2.5 parts of modified nano-alumina were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a first polymer molecule;
[0045] (2) Preparation of the second polymer molecule: 27 parts of hexadecyl methacrylate, 15 parts of p-propanesulfonic acid styrene, 7 parts of 3,7-dimethyl-6-octenoic acid, 0.7 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried to constant weight under vacuum conditions at 60° C. to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; 11 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid, and 2.5 parts of organically modified nano-diatomaceous earth were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a second polymer molecule;
[0046] (3) mixing the first polymer molecules and the second polymer molecules in a weight ratio of 1.15:1, and adding a certain amount of diesel to dissolve the diesel, where the amount of the diesel is sufficient to dissolve the drag reducer;
[0047] Among them, the preparation of modified nano alumina:
[0048] S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding glycidyloxypropyl trimethoxysilane coupling agent under stirring conditions, raising the temperature to 75°C, constant temperature magnetic stirring for 6.5h, and obtaining organosilicon-modified nano-alumina after centrifugation, washing, and drying;
[0049] S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0050] S3. The graphene pretreated in step S2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-alumina prepared in step S1 is added, and the mixture is rapidly stirred at 30°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-alumina with an average particle size of 50-200 nm;
[0051] The weight ratio of nano-alumina, anhydrous ethanol and glycidyloxypropyl trimethoxysilane coupling agent is 1:9:0.15;
[0052] Preparation of organically modified nano-diatomite: dissolve the nano-diatomite in deionized water, add a 25% Na2CO3 solution by mass while stirring at a speed of 2500 r / min until the pH value is stabilized at 10, and simultaneously add propylene glycol alginate in an amount of 1% by weight of the nano-diatomite and let stand to obtain a stable suspension, heat to 35°C, add hexadecyltrimethylammonium bromide solution and isopropanol, react for 6.5 hours, obtain a modified diatomite suspension slurry, centrifuge to obtain a diatomite precipitate, use an ethanol solution to wash away excess Br ions, use AgNO3 to check that no yellow precipitate is produced, dry and grind to obtain organically modified nano-diatomite;
[0053] The weight ratio of nano-diatomaceous earth, hexadecyltrimethylammonium bromide solution and isopropanol is 1:1.5:0.65;
[0054] Preparation of interfacial compatibilizer: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use ultrasonic cell crusher to ultrasonically crush it for 7 minutes, add maleic anhydride dried for 9 hours, continue ultrasonication for 20 minutes, and obtain poly-α-olefin grafted with acid anhydride as interfacial compatibilizer;
[0055] The weight ratio of the poly-α-olefin to the maleic anhydride is 100:3.
[0056] Example 2
[0057] Preparation of drag reducing agent for oil and gas gathering and transportation:
[0058] (1) Preparation of the first polymer molecule: 30 parts by weight of hexadecyl methacrylate, 12 parts by weight of ethylene glycol mono-9-octadecene-1-ether, 10 parts by weight of allyl triethylammonium chloride, 0.5 parts by weight of polyethylene glycol monooctylphenyl ether, and 2 parts by weight of hydroxyethyl cellulose were mixed and added to toluene. The mixture was stirred at a speed of 300 r / min and nitrogen was introduced as a protective gas. 0.1 parts by weight of azobisisoheptanenitrile was added at a temperature of 90° C. The reaction was stopped after 12 h of heating. After cooling, an appropriate amount of anhydrous ethanol was added to precipitate the fraction. After separation, the mixture was washed with anhydrous ethanol for several times, and dried under vacuum at 60° C. to constant weight, to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride; 10 parts of an interfacial compatibilizer were added to a n-heptane solution of the polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride, and then 3 parts of modified nano-alumina were added, and the mixture was uniformly mixed and reacted at 60° C. with low-speed stirring for 2 hours to obtain a first polymer molecule;
[0059] (2) Preparation of the second polymer molecule: 25 parts of hexadecyl methacrylate, 18 parts of p-propanesulfonic acid styrene, 5 parts of 3,7-dimethyl-6-octenoic acid, 1 part of polyethylene glycol monooctylphenyl ether, and 1 part of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 500 r / min. Nitrogen protective gas was introduced, and 0.3 parts of azobisisoheptanenitrile was added at a temperature of 70° C. After reacting for 10 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried to constant weight at 60° C. under vacuum conditions to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; 12 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid, and 2 parts of organically modified nano-diatomaceous earth were added, mixed evenly, and reacted at 80° C. with low-speed stirring for 1 hour to obtain a second polymer molecule;
[0060] (3) mixing the first polymer molecules and the second polymer molecules in a weight ratio of 1.2:1, and adding a certain amount of diesel to dissolve the diesel, where the amount of the diesel is sufficient to dissolve the drag reducer;
[0061] Among them, the preparation of modified nano alumina:
[0062] S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8:1, and adding glycidyloxypropyl trimethoxysilane coupling agent under stirring conditions, raising the temperature to 80°C, constant temperature magnetic stirring for 5 hours, and obtaining organosilicon-modified nano-alumina after centrifugation, washing, and drying;
[0063] S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0064] S3. The graphene pretreated in step S2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-alumina prepared in step S1 is added, and the mixture is rapidly stirred at 35°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-alumina with an average particle size of 50-200 nm;
[0065] The weight ratio of nano-alumina, anhydrous ethanol and glycidyloxypropyl trimethoxysilane coupling agent is 1:8:0.2;
[0066] Preparation of organically modified nano-diatomite: dissolve the nano-diatomite in deionized water, add a 30% Na2CO3 solution with a mass percentage concentration while stirring at a speed of 2000r / min until the pH value is stabilized at 10, and at the same time, add propylene glycol alginate in an amount of 1% by weight of the nano-diatomite and let it stand to obtain a stable suspension state, heat it to 120°C, add hexadecyltrimethylammonium bromide solution and isopropanol, react for 8h, obtain a modified diatomite suspension slurry, centrifuge to obtain a diatomite precipitate, use an ethanol solution to wash away excess Br ions, use AgNO3 to check that no yellow precipitate is produced, dry and grind to obtain organically modified nano-diatomite;
[0067] The weight ratio of nano-diatomaceous earth, hexadecyltrimethylammonium bromide solution and isopropanol is 1:1:0.8;
[0068] Preparation of interfacial compatibilizer: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use ultrasonic cell crusher to ultrasonically crush it for 5 minutes, add maleic anhydride dried for 12 hours, continue ultrasonication for 10 minutes, and obtain poly-α-olefin grafted with acid anhydride as interfacial compatibilizer;
[0069] The weight ratio of the poly-α-olefin to the maleic anhydride is 100:4.
[0070] Example 3
[0071] Preparation of drag reducing agent for oil and gas gathering and transportation:
[0072] (1) Preparation of the first polymer molecule: 25 parts of hexadecyl methacrylate, 18 parts of ethylene glycol mono-9-octadecene-1-ether, 6 parts of allyl triethylammonium chloride, 1 part of polyethylene glycol monooctylphenyl ether, and 1 part of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 500 r / min. Nitrogen protective gas was introduced, and 0.3 parts of azobisisoheptanenitrile was added at a temperature of 70° C. After reacting for 10 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried under vacuum conditions at 60° C. to constant weight, to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride; 12 parts of an interfacial compatibilizer were added to a n-heptane solution of the polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride, and then 2 parts of modified nano-alumina were added, and the mixture was uniformly mixed and reacted at 80° C. with low-speed stirring for 1 hour to obtain a first polymer molecule;
[0073] (2) Preparation of the second polymer molecule: 30 parts of hexadecyl methacrylate, 12 parts of p-propanesulfonic acid styrene, 8 parts of 3,7-dimethyl-6-octenoic acid, 0.5 parts of polyethylene glycol monooctylphenyl ether, and 2 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 300 r / min. Nitrogen protective gas was introduced, and 0.1 parts of azobisisoheptanenitrile was added at a temperature of 90° C. After reacting for 12 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added, and precipitation and separation were performed. Then, the mixture was washed with anhydrous ethanol for several times, and dried to constant weight under vacuum conditions at 60° C. to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; 10 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid, and 3 parts of organically modified nano-diatomaceous earth were added, mixed evenly, and reacted at 60° C. with low-speed stirring for 2 hours to obtain a second polymer molecule;
[0074] (3) mixing the first polymer molecules and the second polymer molecules in a weight ratio of 1.1:1, and adding a certain amount of diesel to dissolve, wherein the amount of diesel is sufficient to dissolve the drag reducer;
[0075] Among them, the preparation of modified nano alumina:
[0076] S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 9:1, and adding glycidyloxypropyltrimethoxysilane coupling agent under stirring conditions, raising the temperature to 70°C, constant temperature magnetic stirring for 8 hours, and obtaining organosilicon-modified nano-alumina after centrifugation, washing, and drying;
[0077] S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0078] S3. The graphene pretreated in step S2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-alumina prepared in step S1 is added, and the mixture is rapidly stirred at 25°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-alumina with an average particle size of 50-200 nm;
[0079] The weight ratio of nano-alumina, anhydrous ethanol and glycidyloxypropyl trimethoxysilane coupling agent is 1:10:0.1;
[0080] Preparation of organically modified nano-diatomite: dissolve the nano-diatomite in deionized water, add a 20% Na2CO3 solution by mass while stirring at a speed of 3000 r / min until the pH value is stabilized at 10, and at the same time, add propylene glycol alginate in an amount of 1% by weight of the nano-diatomite and let it stand to obtain a stable suspension state, heat it to 150°C, add hexadecyltrimethylammonium bromide solution and isopropanol, react for 5 hours, obtain a modified diatomite suspension slurry, centrifuge to obtain a diatomite precipitate, use an ethanol solution to wash away excess Br ions, use AgNO3 to check that no yellow precipitate is produced, dry and grind to obtain organically modified nano-diatomite;
[0081] The weight ratio of nano-diatomaceous earth, hexadecyltrimethylammonium bromide solution and isopropanol is 1:2:0.5;
[0082] Preparation of interfacial compatibilizer: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use ultrasonic cell crusher to ultrasonically crush it for 10 minutes, add maleic anhydride dried for 6 hours, continue ultrasonication for 30 minutes, and obtain poly-α-olefin grafted with acid anhydride as interfacial compatibilizer;
[0083] The weight ratio of the poly-α-olefin to the maleic anhydride is 100:2.
[0084] Example 4
[0085] Preparation of drag reducing agent for oil and gas gathering and transportation:
[0086] (1) Preparation of the first polymer molecule: 27 parts of hexadecyl methacrylate, 14 parts of ethylene glycol mono-9-octadecene-1-ether, 8 parts of allyl triethylammonium chloride, 0.7 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added, and precipitation and separation were performed. Then, the mixture was washed with anhydrous ethanol for several times, and dried under vacuum at 60° C. to constant weight, to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride; 11 parts of an interfacial compatibilizer were added to a n-heptane solution of the polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride, and then 3 parts of modified nano-alumina were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a first polymer molecule;
[0087] (2) Preparation of the second polymer molecule: 28 parts of hexadecyl methacrylate, 15 parts of p-propanesulfonic acid styrene, 7 parts of 3,7-dimethyl-6-octenoic acid, 0.8 parts of polyethylene glycol monooctylphenyl ether, and 1.6 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 85° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried to constant weight under vacuum conditions at 60° C. to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; 11 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid, and 2.5 parts of organically modified nano-diatomaceous earth were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a second polymer molecule;
[0088] (3) mixing the first polymer molecules and the second polymer molecules in a weight ratio of 1.18:1, and adding a certain amount of diesel to dissolve the diesel, where the amount of the diesel is sufficient to dissolve the drag reducer;
[0089] Among them, the preparation of modified nano alumina:
[0090] S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding glycidyloxypropyl trimethoxysilane coupling agent under stirring, raising the temperature to 75°C, constant temperature magnetic stirring for 6 hours, and obtaining organosilicon-modified nano-alumina after centrifugation, washing, and drying;
[0091] S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0092] S3. adding the graphene pretreated in step S2 to ethanol for ultrasonic dispersion, adding the organosilicon-modified nano-alumina prepared in step S1, rapidly stirring at 32°C to allow it to react fully, centrifuging, washing with anhydrous ethanol several times, and vacuum drying, grinding to obtain modified nano-alumina with an average particle size of 50-200 nm;
[0093] The weight ratio of nano-alumina, anhydrous ethanol and glycidyloxypropyl trimethoxysilane coupling agent is 1:9:0.2;
[0094] Preparation of organically modified nano-diatomite: dissolve the nano-diatomite in deionized water, add a 24% Na2CO3 solution by mass while stirring at a speed of 2500 r / min until the pH value is stabilized at 10, and simultaneously add propylene glycol alginate in an amount of 1% by weight of the nano-diatomite and let stand to obtain a stable suspension, heat to 130°C, add hexadecyltrimethylammonium bromide solution and isopropanol, react for 6 hours, obtain a modified diatomite suspension slurry, centrifuge to obtain a diatomite precipitate, use an ethanol solution to wash away excess Br ions, use AgNO3 to check that no yellow precipitate is produced, dry and grind to obtain organically modified nano-diatomite;
[0095] The weight ratio of nano-diatomaceous earth, hexadecyltrimethylammonium bromide solution and isopropanol is 1:1.4:0.6;
[0096] Preparation of interfacial compatibilizer: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use ultrasonic cell crusher to ultrasonically crush it for 8 minutes, add maleic anhydride dried for 10 hours, continue ultrasonication for 25 minutes, and obtain poly-α-olefin grafted with acid anhydride as interfacial compatibilizer;
[0097] The weight ratio of the poly-α-olefin to the maleic anhydride is 100:3.
[0098] Comparative Example 1
[0099] Preparation of drag reducing agent for oil and gas gathering and transportation:
[0100] (1) Preparation of the first polymer molecule: 36 parts of hexadecyl methacrylate, 15 parts of ethylene glycol mono-9-octadecene-1-ether, 0.8 parts of polyethylene glycol mono-octylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and the mixture was continuously stirred at a speed of 400 r / min, and nitrogen protective gas was introduced. 0.2 parts of azobisisoheptanenitrile was added at a temperature of 80° C., and the heating was stopped after the reaction for 11 hours. After cooling, an appropriate amount of anhydrous ethanol was added, and after precipitation and separation, the mixture was washed with anhydrous ethanol for multiple times, and dried at 60° C. under vacuum conditions to constant weight to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether; 11 parts of an interfacial compatibilizer were added to the n-heptane solution of the polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether, and 2.5 parts of modified nano-alumina were added. After mixing evenly, the mixture was stirred at a low speed at 70° C. for 1.5 hours to obtain a first polymer molecule;
[0101] (2) Preparation of the second polymer molecule: 27 parts of hexadecyl methacrylate, 15 parts of p-propanesulfonic acid styrene, 7 parts of 3,7-dimethyl-6-octenoic acid, 0.7 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried to constant weight under vacuum conditions at 60° C. to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; 11 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid, and 2.5 parts of organically modified nano-diatomaceous earth were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a second polymer molecule;
[0102] (3) mixing the first polymer molecules and the second polymer molecules in a weight ratio of 1.15:1, and adding a certain amount of diesel to dissolve the diesel, where the amount of the diesel is sufficient to dissolve the drag reducer;
[0103] Among them, the preparation of modified nano alumina:
[0104] S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding glycidyloxypropyl trimethoxysilane coupling agent under stirring conditions, raising the temperature to 75°C, constant temperature magnetic stirring for 6.5h, and obtaining organosilicon-modified nano-alumina after centrifugation, washing, and drying;
[0105] S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0106] S3. The graphene pretreated in step S2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-alumina prepared in step S1 is added, and the mixture is rapidly stirred at 30°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-alumina with an average particle size of 50-200 nm;
[0107] The weight ratio of nano-alumina, anhydrous ethanol and glycidyloxypropyl trimethoxysilane coupling agent is 1:9:0.15;
[0108] Preparation of organically modified nano-diatomite: dissolve the nano-diatomite in deionized water, add a 25% Na2CO3 solution by mass while stirring at a speed of 2500 r / min until the pH value is stabilized at 10, and simultaneously add propylene glycol alginate in an amount of 1% by weight of the nano-diatomite and let stand to obtain a stable suspension, heat to 35°C, add hexadecyltrimethylammonium bromide solution and isopropanol, react for 6.5 hours, obtain a modified diatomite suspension slurry, centrifuge to obtain a diatomite precipitate, use an ethanol solution to wash away excess Br ions, use AgNO3 to check that no yellow precipitate is produced, dry and grind to obtain organically modified nano-diatomite;
[0109] The weight ratio of nano-diatomaceous earth, hexadecyltrimethylammonium bromide solution and isopropanol is 1:1.5:0.65;
[0110] Preparation of interfacial compatibilizer: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use ultrasonic cell crusher to ultrasonically crush it for 7 minutes, add maleic anhydride dried for 9 hours, continue ultrasonication for 20 minutes, and obtain poly-α-olefin grafted with acid anhydride as interfacial compatibilizer;
[0111] The weight ratio of the poly-α-olefin to the maleic anhydride is 100:3.
[0112] Comparative Example 2
[0113] Preparation of drag reducing agent for oil and gas gathering and transportation:
[0114] (1) Preparation of the first polymer molecule: 28 parts of hexadecyl methacrylate, 15 parts of ethylene glycol mono-9-octadecene-1-ether, 8 parts of allyl triethylammonium chloride, 0.8 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried under vacuum conditions at 60° C. to constant weight to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride; 11 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride, and 2.5 parts of modified nano-alumina were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a first polymer molecule;
[0115] (2) Preparation of the second polymer molecule: 27 parts of hexadecyl methacrylate, 15 parts of p-propanesulfonic acid styrene, 7 parts of 3,7-dimethyl-6-octenoic acid, 0.7 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80°C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, it was washed with anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions to constant weight to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; 11 parts of an interfacial compatibilizer were added to the n-heptane solution of the polymer hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid, mixed evenly, and reacted at 70°C with low-speed stirring for 1.5 hours to obtain a second polymer molecule;
[0116] (3) mixing the first polymer molecules and the second polymer molecules in a weight ratio of 1.15:1, and adding a certain amount of diesel to dissolve the diesel, where the amount of the diesel is sufficient to dissolve the drag reducer;
[0117] Among them, the preparation of modified nano alumina:
[0118] S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water in a mass ratio of 8.5:1, and adding glycidyloxypropyl trimethoxysilane coupling agent under stirring conditions, raising the temperature to 75°C, constant temperature magnetic stirring for 6.5h, and obtaining organosilicon-modified nano-alumina after centrifugation, washing, and drying;
[0119] S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed;
[0120] S3. The graphene pretreated in step S2 is added to ethanol for ultrasonic dispersion, and the organosilicon-modified nano-alumina prepared in step S1 is added, and the mixture is rapidly stirred at 30°C for full reaction, centrifuged, washed several times with anhydrous ethanol, and then vacuum dried, and ground to obtain modified nano-alumina with an average particle size of 50-200 nm;
[0121] The weight ratio of nano-alumina, anhydrous ethanol and glycidyloxypropyl trimethoxysilane coupling agent is 1:9:0.15;
[0122] Preparation of interfacial compatibilizer: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use ultrasonic cell crusher to ultrasonically crush it for 7 minutes, add maleic anhydride dried for 9 hours, continue ultrasonication for 20 minutes, and obtain poly-α-olefin grafted with acid anhydride as interfacial compatibilizer;
[0123] The weight ratio of the poly-α-olefin to the maleic anhydride is 100:3.
[0124] Comparative Example 3
[0125] Preparation of drag reducing agent for oil and gas gathering and transportation:
[0126] (1) Preparation of the first polymer molecule: 28 parts of hexadecyl methacrylate, 15 parts of ethylene glycol mono-9-octadecene-1-ether, 8 parts of allyl triethylammonium chloride, 0.8 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, anhydrous ethanol was used to separate the mixture. The mixture was washed with alcohol for multiple times, and dried under vacuum at 60° C. to constant weight to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride; 11 parts of an interfacial compatibilizer were added to a n-heptane solution of the polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride, and 2.5 parts of nano-alumina with an average particle size of 50-200 nm were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a first polymer molecule;
[0127] (2) Preparation of the second polymer molecule: 27 parts of hexadecyl methacrylate, 15 parts of p-propanesulfonic acid styrene, 7 parts of 3,7-dimethyl-6-octenoic acid, 0.7 parts of polyethylene glycol monooctylphenyl ether, and 1.5 parts of hydroxyethyl cellulose were mixed and added to toluene according to weight parts, and stirred continuously at a speed of 400 r / min. Nitrogen protective gas was introduced, and 0.2 parts of azobisisoheptonitrile was added at a temperature of 80° C. After reacting for 11 hours, heating was stopped, and after cooling, an appropriate amount of anhydrous ethanol was added. After precipitation and separation, The mixture was then washed with anhydrous ethanol for multiple times, and dried to constant weight under vacuum conditions at 60° C. to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; 11 parts of an interfacial compatibilizer were added to an n-heptane solution of the polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid, and 2.5 parts of organically modified nano-diatomaceous earth were added, and the mixture was uniformly mixed and reacted at 70° C. with low-speed stirring for 1.5 hours to obtain a second polymer molecule;
[0128] (3) mixing the first polymer molecules and the second polymer molecules in a weight ratio of 1.15:1, and adding a certain amount of diesel to dissolve the diesel, where the amount of the diesel is sufficient to dissolve the drag reducer;
[0129] Among them, the preparation of organic modified nano diatomite: dissolve the nano diatomite in deionized water, add a 25% Na2CO3 solution with a mass percentage concentration while stirring at a speed of 2500r / min until the pH value is stabilized at 10, and at the same time, add propylene glycol alginate in an amount of 1% by weight of the nano diatomite and let it stand to obtain a stable suspension state, heat it to 35°C, add hexadecyltrimethylammonium bromide solution and isopropanol, react for 6.5h, obtain a modified diatomite suspension slurry, centrifuge to obtain a diatomite precipitate, use an ethanol solution to wash away excess Br ions, use AgNO3 to check that no yellow precipitate is produced, dry and grind to obtain organic modified nano diatomite;
[0130] The weight ratio of nano-diatomaceous earth, hexadecyltrimethylammonium bromide solution and isopropanol is 1:1.5:0.65;
[0131] Preparation of interfacial compatibilizer: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use ultrasonic cell crusher to ultrasonically crush it for 7 minutes, add maleic anhydride dried for 9 hours, continue ultrasonication for 20 minutes, and obtain poly-α-olefin grafted with acid anhydride as interfacial compatibilizer;
[0132] The weight ratio of the poly-α-olefin to the maleic anhydride is 100:3.
[0133] Experimental example
[0134] The drag reducers for oil and gas gathering and transportation prepared in Examples 1-4 and Comparative Examples 1-3 were taken to test the initial drag reduction rate and the drag reduction rate after shearing for 10 minutes and 20 minutes, respectively.
[0135] The test data is shown in Table 1 below:
[0136] Table 1
[0137]
[0138] It can be seen from Table 1 that the drag reducing agents for oil and gas gathering and transportation prepared in Examples 1-4 of the present application have good drag reduction rates and shear resistance.
[0139] In Comparative Example 1, allyl triethylammonium chloride in the raw material of the first polymer molecule was replaced with an equal weight of hexadecyl methacrylate, and the rest was the same as in Example 1. The drag reduction rate and shear resistance of the drag reducer for oil and gas gathering and transportation prepared in Comparative Example 1 were significantly reduced, indicating that the addition of the quaternary ammonium salt group of the present application can not only enhance the intermolecular association, but also adjust the solubility of the drag reducer molecules, thereby improving the drag reduction effect of the drag reducer.
[0140] The raw material of the second polymer molecule of Comparative Example 2 does not contain organically modified nano-diatomite, and the rest is the same as Example 1. The shear resistance of the drag reducer for oil and gas gathering and transportation prepared in Comparative Example 2 is significantly reduced, indicating that the present application introduces organically modified nano-diatomite into the drag reducer to form a nano-composite polymer, which can increase the rigidity and strength of the polymer, and further improve the shear resistance of the drag reducer.
[0141] In Comparative Example 3, ordinary nano-alumina is used instead of modified nano-alumina in the raw material of the first polymer molecule, and the rest is the same as Example 1. The drag reduction rate and shear resistance of the drag reducer for oil and gas gathering and transportation prepared in Comparative Example 3 are significantly reduced, indicating that modified alumina can improve the rigidity of the nano-composite polymer, thereby enhancing the shear strength of the nano-composite polymer. At the same time, the carboxylation treatment of the modified silicone and graphene surfaces can affect the solubility of the first polymer molecules, thereby improving the drag reduction rate.
[0142] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.
Claims
1. A drag reducing agent for oil and gas gathering and transportation, characterized in that: comprising a first polymer molecule and a second polymer molecule, wherein the first polymer molecule and the second polymer molecule are combined by intermolecular association; The first polymer molecule comprises the following raw materials in parts by weight: 25-30 parts of hexadecyl methacrylate, 12-18 parts of ethylene glycol mono-9-octadecene-1-ether, 6-10 parts of allyl triethylammonium chloride, 0.1-0.3 parts of azobisisoheptonitrile, 0.5-1 parts of polyethylene glycol monooctylphenyl ether, 1-2 parts of hydroxyethyl cellulose, 2-3 parts of modified nano-alumina, and 10-12 parts of an interfacial compatibilizer; The second polymer molecule comprises the following raw materials in parts by weight: 25-30 parts of hexadecyl methacrylate, 12-18 parts of p-propanesulfonic acid styrene, 5-8 parts of 3,7-dimethyl-6-octenoic acid, 0.1-0.3 parts of azobisisoheptonitrile, 0.5-1 parts of polyethylene glycol monooctylphenyl ether, 1-2 parts of hydroxyethyl cellulose, 2-3 parts of organically modified nano-diatomaceous earth, and 10-12 parts of an interfacial compatibilizer.
2. The drag reducing agent for oil and gas gathering and transportation according to claim 1, characterized in that: The weight ratio of the first polymer molecules to the second polymer molecules is (1.1-1.2):
1.
3. The drag reducing agent for oil and gas gathering and transportation according to claim 1, characterized in that: The preparation of the first polymer molecule comprises the following steps: A1. According to parts by weight, hexadecyl methacrylate, ethylene glycol mono-9-octadecene-1-ether, allyl triethylammonium chloride, polyethylene glycol monooctylphenyl ether, and hydroxyethyl cellulose were mixed and added to toluene, stirred at a speed of 300-500r / min, nitrogen protective gas was introduced, azobisisoheptanenitrile was added at a temperature of 70-90°C, the reaction was stopped after 10-12h of heating, and an appropriate amount of anhydrous ethanol was added after cooling. After precipitation and separation, it was washed with anhydrous ethanol several times, and dried to constant weight under vacuum conditions at 60°C to obtain a polymer of hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride; A2. Add the interfacial compatibilizer to the n-heptane solution of the polymer hexadecyl methacrylate-ethylene glycol mono-9-octadecene-1-ether-allyl triethylammonium chloride according to parts by weight, then add the modified nano-alumina, mix well, and react with low-speed stirring at 60-80°C for 1-2h to obtain the first polymer molecule.
4. The drag reducing agent for oil and gas gathering and transportation according to claim 1, characterized in that: The preparation of the second polymer molecule comprises the following steps: B1. Hexadecyl methacrylate, p-propanesulfonic acid styrene, 3,7-dimethyl-6-octenoic acid, polyethylene glycol monooctylphenyl ether, and hydroxyethyl cellulose were mixed and added to toluene in parts by weight, stirred continuously at a speed of 300-500 r / min, nitrogen protective gas was introduced, azobisisoheptanenitrile was added at a temperature of 70-90°C, the reaction was stopped after 10-12h of heating, and an appropriate amount of anhydrous ethanol was added after cooling, and the mixture was precipitated and separated and then washed with anhydrous ethanol several times, and dried to constant weight under vacuum conditions at 60°C to obtain a polymer of hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid; B2. Add the interfacial compatibilizer to the n-heptane solution of the polymer hexadecyl methacrylate-p-propanesulfonic acid styrene-3,7-dimethyl-6-octenoic acid according to weight parts, then add the organically modified nano-diatomaceous earth, mix well, and react with low-speed stirring at 60-80° C. for 1-2 hours to obtain the second polymer molecule.
5. The drag reducing agent for oil and gas gathering and transportation according to claim 1, characterized in that: The preparation of the modified nano-alumina comprises the following steps: S1. Ultrasonic dispersion of nano-alumina in a mixed solution of anhydrous ethanol and deionized water (8-9):1 by mass ratio, and adding glycidyloxypropyl trimethoxysilane coupling agent under stirring, raising the temperature to 70-80°C, constant temperature magnetic stirring for 5-8h, centrifuging, washing, and drying to obtain organosilicon-modified nano-alumina; S2. Graphene pretreatment: Graphene is ultrasonically dispersed in a mixed solution of sulfuric acid and nitric acid, then refluxed at 80°C for 4h, and dried and ground after the reaction is completed; S3. Add the graphene pretreated in step S2 to ethanol for ultrasonic dispersion, add the organosilicon-modified nano-alumina prepared in step S1, stir rapidly at 25-35°C to allow it to react fully, centrifuge, wash several times with anhydrous ethanol, dry in vacuum, and grind to obtain modified nano-alumina.
6. The drag reducing agent for oil and gas gathering and transportation according to claim 5, characterized in that: The weight ratio of the nano-alumina, the anhydrous ethanol and the glycidyloxypropyltrimethoxysilane coupling agent is 1:(8-10):(0.1-0.2).
7. The drag reducing agent for oil and gas gathering and transportation according to claim 1, characterized in that: The preparation of the organic modified nano diatomite comprises the following steps: Nano-diatomite was dissolved in deionized water, and Na2CO3 solution was added dropwise while stirring until the pH value was stabilized at 10. Propylene glycol alginate was added dropwise and allowed to stand to obtain a stable suspension. The temperature was raised to 120-150°C, and hexadecyltrimethylammonium bromide solution and isopropanol were added. The reaction was performed for 5-8 hours to obtain a modified diatomite suspension slurry. The diatomite was centrifuged to obtain a diatomite precipitate. An ethanol solution was used to wash away excess Br ions. AgNO3 was used to check that no yellow precipitate was produced. The organically modified nano-diatomite was dried and ground.
8. The drag reducing agent for oil and gas gathering and transportation according to claim 1, characterized in that: The preparation of the interfacial compatibility agent comprises the following steps: Take poly-α-olefin, add anhydrous ethanol to completely disperse it, use an ultrasonic cell crusher to ultrasonically crush it for 5-10 minutes, add maleic anhydride dried for 6-12 hours, and continue ultrasonicating for 10-30 minutes to obtain poly-α-olefin grafted with acid anhydride as an interfacial compatibilizer.
9. Use of the drag reducing agent for oil and gas gathering and transportation as claimed in any one of claims 1 to 8 in oil gathering and transportation.
10. The use of a drag reducing agent for oil and gas gathering and transportation according to claim 9, characterized in that: The oil products include crude oil, gasoline, kerosene or diesel.
Citation Information
Patent Citations
Resistance reducing agent and preparation method thereof
CN112142909A
Associative oil-soluble high polymer drag reducer and application thereof
CN113004644A
Modified nano SiO2 composite oil drag reducer as well as preparation method and application thereof
CN117821140A
Miniemulsion polymerization to prepare drag reducers
US20110184121A1
Drag reducing agent
US20230227740A1